If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2y = 23.52 Solving 6x + 2y = 23.52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 6x + 2y + -2y = 23.52 + -2y Combine like terms: 2y + -2y = 0 6x + 0 = 23.52 + -2y 6x = 23.52 + -2y Divide each side by '6'. x = 3.92 + -0.3333333333y Simplifying x = 3.92 + -0.3333333333y
| -8+15+-2+-15+-4+13+-17+11= | | 6k-3-2k=k-22 | | x*x-14x+33=0 | | -5=-2-3 | | -6z=3x | | x=-7+7 | | 7-8x=87-43x | | 2x-8y=-11 | | 30x*-6= | | 20x-45= | | -7x+5=48+x+45 | | y=-2(-7+y)+7 | | 2x-y+2z=-8 | | 2x^2+x-3=18 | | 4(7x-1)=5(2x+1) | | (2x-17)+1x+59=360 | | 4x+20=45-x | | x=18+-7(2) | | 2x-2=-8+3x | | 5(y-3)-3(y-2)=8 | | (3)/(8)x-(1)/(4)=2 | | 40-x=12x | | 48=4n/7+n | | -8(-3)(-3)= | | y=-4(18+-7y)+18 | | 4z-11-z+2=0 | | -2x(5x-8)=6x | | 8a+3=3 | | 9x-1=125 | | 1/8(5x+4)=3.4 | | (1)/(8)x=(1)/(2) | | (x-5)/(3*x)+(6/2*x+1)=0 |